The Practice of Nusyuz Among Tanjungbalai Tni from the Perspective of the Indonesian Ulama Council of Tanjungbalai (Case Study at Tni Lumba-Lumba Complex Tanjung Balai) - Nailah, Dea Anjani; Irwan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to examine the forms of behavior and factors that cause nusyuz among the TNI in the review of Islamic law as well as how the TNI Council's settlement mechanism for nusyuz behavior. The urgency of this problem lies in the complexity of TNI household relationships that often face challenges due to heavy military duties and have an impact on family harmony. Based on this background, this research uses a qualitative method with a legal sociology approach, where primary data is obtained through interviews while secondary data comes from Islamic legal literature and previous research results. The results show that the wife's disobedience in the TNI household does not necessarily make the wife immediately blamed, but it is necessary to first investigate the causes, including the possibility of the husband's actions triggering the disobedience. In the legal process, the wife's rights are still protected until the official divorce decision is issued. This research emphasizes that the concept of nusyuz in the context of the TNI requires a fair legal approach and clear procedures.